Metastatic Malignant Melanoma of the Gastrointestinal Tract: A Rare Case and Review of Current Literature - Julian Iñaki L. Garcia; Jennielyn C. Agcaoli-Conde; Dexter Santos (Journal of Clinical Case Reports and Images, 2022)
Malignant melanoma the most common malignancies associated with GI involvement. They usually manifest clinically at an advanced stage of neoplasm. Surgery is also recommended for palliative treatment of GIT metastases. A case of a 67-year-old male diagnosed with malignant melanoma for 7 months had burning epigastric pain and bloatedness. Esophagogastroduodenoscopy showed multiple flat lesions. Biopsy findings were consistent with malignant melanoma. Malignant melanoma has an early tendency to metastasize and has a high mortality rate due to its complications. In patients with malignant melanoma since Gastrointestinal involvement is now being documented as part of metastatic work up esophagogastroduodenoscopy is suggested as an important tool in the treatment and patient’s +outcome. Although metastases to the stomach is rare, it is essential to be thorough and include an upper endoscopy to rule out metastatic disease, especially in symptomatic patients.
Keywords: Malignant Melanoma